2021
DOI: 10.3389/fcell.2021.679866
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Studies of Human Cord Blood Derived Mononuclear Cells and Umbilical Cord Derived Mesenchyme Stem Cells in Ameliorating Bronchopulmonary Dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is a common pulmonary complication observed in preterm infants that is composed of multifactorial pathogenesis. Current strategies, albeit successful in moderately reducing morbidity and mortality of BPD, failed to draw overall satisfactory conclusion. Here, using a typical mouse model mimicking hallmarks of BPD, we revealed that both cord blood-derived mononuclear cells (CB-MNCs) and umbilical cord-derived mesenchymal stem cells (UC-MSCs) are efficient in alleviating BPD. Nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“… 48 , 51 , 53 , 55 All 8 papers that analyzed for a difference in the survival of animals receiving UCB-derived therapy compared to injury controls reported no significant difference. 39 , 40 , 42 , 46 , 47 , 49 , 52 , 60 Thirteen preclinical studies reported the outcome of weight in UCB-derived therapy group versus injury control group. Six of the 13 studies reported a statistically significant difference in favor of UCB-derived therapy administration being associated with a higher weight when compared to the injury control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 48 , 51 , 53 , 55 All 8 papers that analyzed for a difference in the survival of animals receiving UCB-derived therapy compared to injury controls reported no significant difference. 39 , 40 , 42 , 46 , 47 , 49 , 52 , 60 Thirteen preclinical studies reported the outcome of weight in UCB-derived therapy group versus injury control group. Six of the 13 studies reported a statistically significant difference in favor of UCB-derived therapy administration being associated with a higher weight when compared to the injury control group.…”
Section: Resultsmentioning
confidence: 99%
“… 39 , 41 , 42 , 51 , 52 , 55 , 56 Finally, 8 preclinical studies investigated other safety effects associated with the administration of UCB. 39 , 43-45 , 49 , 51 , 55 , 57 Two of the 8 studies reported a difference in safety effects. De Paepe et al observed lung tumors in 1 normal control mouse and 2 preterm lung injury mice which received UCB-derived CD34 + cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stromal cells (MSCs) isolated from TA of newborns express lung-specific genes, differ from lung fibroblasts, and produce proinflammatory cytokines [ 92 ]. In a newborn mouse lung injury model, intravenous or intra-alveolar MSCs transplantation was related to decreased inflammation and fibrosis in the lung [ 93 ]. The colony/cluster ratio of MSCs in the TA was considerably lower in BPD infants, according to a cross-sectional investigation (p=0.002).…”
Section: Biofluid Biomarkersmentioning
confidence: 99%
“…Compared with MNCs obtained from adult bone marrow MNCs (BMMNCs), umbilical cord blood MNCs (UCMNCs) have higher cell viability and lower reaction to cytotoxic T cells and T-helper (Th)1 cells ( 5 ). The therapeutic potential of UCMNCs has been reported in many animal models involving bronchopulmonary dysplasia ( 6 ), neonatal lung injury ( 7 ), and acute myocardial infarction ( 8 ), and in some clinical studies for diseases such as multiple system atrophy ( 9 ) and spastic cerebral palsy ( 10 ). The non-invasiveness, high accessibility, and few ethical constraints of UCMNCs make them a suitable alternative to BMMNCs.…”
Section: Introductionmentioning
confidence: 99%